The Impact of Organizational Culture, Work Ethics, and Organizational Commitment on Employee Retention in a Regional Revenue Agency: A Case Study - Suharto, Aan (Yayasan Sinergi Kawula Muda, 2025)
This study aims to analyze the factors affecting employee retention, focusing on organizational culture, work ethics ethics, and commitment to the organization. Employee retention is a major challenge for companies in a competitive and dynamic labor market. Organizational culture reflects the values, norms, and expectations upheld by all members of the organization, creating a comfortable and supportive work environment. Work ethics emphasize morals and behavioral standards that guide actions and decisions within the company, helping to build a foundation of ethical conduct and integrity. Additionally, employee commitment to the organization forms the basis for loyalty and engagement in achieving organizational goals. This study uses a quantitative method with an associative approach to identify relationships between variables. Data was obtained through questionnaires distributed to 36 employees at the Regency X Regional Revenue Agency, using a census sample. The results show that only organizational commitment has a significant influence on employee retention at a 95% confidence level, providing the largest contribution in explaining variations in employee retention. Organizational culture and workethics are not significant, so their contributions are minimal, explaining why the Adjusted R² value is lower than the R². Overall, the model has moderate predictive power for employee retention but could be improved by adding more relevant variables. These findings imply that companies should focus more on internal factors that can build employee loyalty and retain top talent